PENGEMBANGAN MEDIA BUKU CERITA BERGAMBAR DIGITAL UNTUK MENINGKATKAN KEMAMPUAN MEMBACA ANAK USIA DINI - Nurwenda, Dewi; Candra Nindiya, Devi; Muzayin Shofwan, Arif (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the low interest and early reading ability of young children, as well as the limited variety of instructional media used in classrooms. The objective of this research is to develop a digital illustrated storybook media that is valid, practical, and effective in improving early childhood reading skills. This study employs a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. Data were collected through observation, interviews, questionnaires, tests, and documentation, and analyzed using both qualitative and quantitative techniques. The results indicate that the developed media is categorized as highly valid based on expert validation, practical for teachers to use, and effective in enhancing children's reading abilities. This improvement is reflected in children's ability to recognize letters, read syllables and simple words, understand story content, and increased learning interest and participation. Therefore, the digital illustrated storybook media can serve as an innovative alternative in early reading instruction and has implications for improving the quality of learning to be more interactive, engaging, and appropriate to early childhood characteristics.